Effect of Cadmium chloride on the Liver, kidney and heart tissues and the protective role of pomegranate seed oil in male Albino rats. - Rashid Khamees Shaban; Mohammed Khalil Ibrahim; Qasim Azeez Razooqi (Tikrit Journal of Pure Science, 2020)
This experiment was designed to identify the protective role of pomegranate seed oil against the toxicity of Cadmium chloride on the tissues of the liver, kidneys and heart, as it distributed 24 male rats to four groups. The results of microscopic examination of the target organs tissues many of histological lesions after treating animals with Cadmium chloride represented by necrosis, fatty degeneration and fibrosis around the central vein in the liver tissue, swelling of the glomeruli, necrosis of kidney tissue, necrosis within the myocardial fibers and hemorrhage within heart tissue .